Prevalence of Depression among Infertile Couples Attending a Tertiary-Care Infertility Clinic - Gayathri S Hari; Indu D; Parvathi S Hari; Sudha P (University Library System, University of Pittsburgh, 2023)
BACKGROUND: A large number of people are affected by infertility in their life time indicating that this is a major health challenge globally. Infertility is currently being thought-about as a medical and social condition which can cause social, emotional and psychological distress. It is estimated that psychological factors have an important role in the pathogenesis of infertility.  Although depression has been described as a common consequence of infertility, very little has been documented related to its prevalence and severity, especially in India. This might be because those who fall outside the normal range of depression inventories are poorly reported or because of the fact that the psychological impact of infertility differs from that due to other medical conditions. Addressing the psychological issues during infertility treatment is now considered important. This is because of the increasing awareness that depression could be the cause of infertility, its consequence, or both and may interfere success of infertility treatment and the ability to tolerate on-going treatment. Treatments for infertility have effects on estrogen and progesterone levels. These hormones influence mood of the woman through their actions on serotonin. On the other hand emotional distress itself can suppress ovarian function or implantation resulting in decreased fertility and reduced response to its treatment. This interaction creates a vicious circle between depression and infertile status and can result in treatment dropouts or treatment failure.  This study aimed to assess the prevalence of depression among infertile couples attending a tertiary care infertility clinic. METHODS: A Hospital based cross sectional study was conducted and a calculated sample of 126 couples with infertility attending the infertility clinic were consecutively enrolled into the study after obtaining consent. Data was collected using an interviewer-administered semi-structured questionnaire and depression was assessed using PHQ9 depression tool. A couple was considered to have depression if at least one of the partners had depression.  Data was analysed using SPSS version 16. Quantitative variables were expressed as mean and standard deviation and qualitative variables as proportions. Chi-square test of independence and Fisher's Exact Test were used to test the association between categorical variables. RESULTS: The prevalence of depression among infertile couples was 51.6 %( n=65). Depression was more prevalent in females (48.4% n=61) than in males (33.3% n=42) and when the reason for infertility was female-related. There was a significant risk of development of depression when the other partner had depression (p=0.001, Odds ratio=25.196). CONCLUSION: Females are often blamed for childlessness especially in rural India resulting in an increased prevalence of depression among infertile females. Efforts should be taken to educate people about infertility so that there is less pressure on infertile couples.  Counseling methods, especially supportive psychotherapy and interventions to decrease and prevent the development of severe depression among these patients should be considered.